Analisis Biaya Fuel Consumption Alat Angkut Dump Truck dalam Aktivitas Pengangkutan Overburden PIT A9 PT. Mitra Abadi Mahakam Jobsite PT. Bukit Baiduri Energi - Fajar Ramadhan; Harjuni Hasan; Albertus Juvensius Pontus; Henny Magdalena; Ardhan Ismail (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Mitra Abadi Mahakam as a contractor operating at PT. Bukit Baiduri Energi's jobsite, especially in the Pit A9 area, faces operational challenges related to variations in haul road grades. Differences in road gradients on the overburden hauling route have the potential to cause significant differences in fuel consumption between dump truck units, which ultimately affects the overall efficiency of hauling activities. The study was conducted quantitatively with primary and secondary data requirements and through 3 stages. The study resulted in an average fuel consumption value in loaded conditions of 1.41 liters and in unloaded conditions of 0.18 liters. The average fuel ratio value in loaded conditions was 0.62 liters/second and in unloaded conditions of 0.32 liters/second. The cost of fuel consumption in loaded conditions was Rp. 4,972,800 (301.92) and in unloaded conditions of Rp. 2,607,360 (158.30)